2021
DOI: 10.2147/dddt.s292805
|View full text |Cite
|
Sign up to set email alerts
|

Withanone from Withania somnifera Attenuates SARS-CoV-2 RBD and Host ACE2 Interactions to Rescue Spike Protein Induced Pathologies in Humanized Zebrafish Model

Abstract: SARS-CoV-2 engages human ACE2 through its spike (S) protein receptor binding domain (RBD) to enter the host cell. Recent computational studies have reported that withanone and withaferin A, phytochemicals found in Withania somnifera, target viral main protease (M Pro) and host transmembrane TMPRSS2, and glucose related protein 78 (GRP78), respectively, implicating their potential as viral entry inhibitors. Absence of specific treatment against SARS-CoV-2 infection has encouraged exploration of phytochemicals a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 70 publications
1
41
0
Order By: Relevance
“… David et al, 2021 in their MedRixv preprint showed that a common variant of TMPRSS2 protects against COVID-19. In silico screening of several phytochemicals identified that Withanone, one of the constituents of ashwagandha, showed a potential inhibition of ACE2 ( Balkrishna et al, 2021 ). Additionally, Ghosh et al (2021) used molecular dynamic simulations and pharmacophore modeling approaches to predict the highly potent small-molecule derivative of withaferin A that potentially inhibits SARS-CoV-2 protease (Mpro), a favorable future therapeutic against COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“… David et al, 2021 in their MedRixv preprint showed that a common variant of TMPRSS2 protects against COVID-19. In silico screening of several phytochemicals identified that Withanone, one of the constituents of ashwagandha, showed a potential inhibition of ACE2 ( Balkrishna et al, 2021 ). Additionally, Ghosh et al (2021) used molecular dynamic simulations and pharmacophore modeling approaches to predict the highly potent small-molecule derivative of withaferin A that potentially inhibits SARS-CoV-2 protease (Mpro), a favorable future therapeutic against COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The stress subscale was assessed from questions 1, 6, 8, 11, 12, 14, and 18. The total score of stress subscale was subdivided into normal (0−10), mild (11)(12)(13)(14)(15)(16)(17)(18), moderate (19)(20)(21)(22)(23)(24)(25)(26), severe (27)(28)(29)(30)(31)(32)(33)(34), and extremely severe stress (35)(36)(37)(38)(39)(40)(41)(42). The DASS-21 has been demonstrated as valid and reliable for assessing mental health in previous COVID-19 related researches in the Indian population.…”
Section: Psychological Health (Depression Anxiety and Stress)mentioning
confidence: 99%
“…These formulations have been shown to suppress inflammatory storm, modulate immune function and reduce lung injury caused by SARS-CoV-2 S-protein under in-vitro and in-vivo experimental conditions. [12][13][14][15] The fundamental research and clinical study with its constituents showed that Divya-Swasari-Coronil-Kit promising bidirectional regulation in the symptoms associated with SARS-CoV-2 infection. Results from a doubleblind, randomized, controlled trial showed expedite virological clearance and concomitantly reduce the risk of viral dissemination.…”
Section: Introductionmentioning
confidence: 99%
“…Further, withanolides from Withania somnifera, showed anti-viral activity for Human Papilloma Virus, influenza viruses, herpes simplex virus, sindbis virus, parainfuenze-3 virus, human cytomegalovirus, and dengue virus type-2 (Amoros et al, 1994;Cai et al, 2015;Kwon et al, 2020;Latheef et al, 2017;Lyu et al, 2005;Munagala et al, 2011;Serkedjieva et al, 1992;Zandi et al, 2011). Withanone from Withania somnifera was also observed to interact with main protease (Mpro) and spike protein of SARS-CoV-2 (Kumar et al, 2020;Tripathi et al, 2020;Balkrishna et al, 2021).…”
Section: Introductionmentioning
confidence: 98%